2011
DOI: 10.1002/jbm.b.31883
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the viscoelastic mechanical behavior of agarose and poly(ethylene glycol) hydrogels

Abstract: This study presents a comparative investigation into differences in the mechanical properties between two hydrogels commonly used in cartilage tissue engineering [agarose vs. poly(ethylene glycol) (PEG)], but which are formed through distinctly different crosslinking mechanisms (physical vs. covalent, respectively). The effects of hydrogel chemistry, precursor concentration, platen type (nonporous vs. porous) used in compression bioreactors, and degradation (for PEG) on the swelling properties and static and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 66 publications
(134 reference statements)
12
52
2
Order By: Relevance
“…This is in good agreement with recent results reported by Shapiro and Oyen (Shapiro and Oyen, 2014) and Roberts et al (Roberts et al, 2011), who showed that the elastic modulus of PEG hydrogels increases with increasing the total polymer concentration.…”
Section: Viscoelastic Properties Of Hydrogelssupporting
confidence: 93%
See 4 more Smart Citations
“…This is in good agreement with recent results reported by Shapiro and Oyen (Shapiro and Oyen, 2014) and Roberts et al (Roberts et al, 2011), who showed that the elastic modulus of PEG hydrogels increases with increasing the total polymer concentration.…”
Section: Viscoelastic Properties Of Hydrogelssupporting
confidence: 93%
“…n agreement with other reports (Nayar et al, 2012;Oyen, 2013;Roberts et al, , the storage modulus of the hydrogel samples increased with increasing polymer concentration. This is evidenced by the lower ‫'ܧ‬ obtained for H30/700 in comparison to those obtained for H50/750 and H50/1000 (see Table 2).…”
Section: Storage Modulus ‫)'ܧ(‬supporting
confidence: 93%
See 3 more Smart Citations